Elevated murine HB-EGF confers sensitivity to diphtheria toxin in EGFR-mutant lung adenocarcinoma - Camila Robles-Oteiza; Deborah Ayeni; Stellar Levy; Robert J. Homer; Susan M. Kaech; Katerina Politi (The Company of Biologists, 2021)
Conditional ablation of defined cell populations in vivo can be achieved using genetically engineered mice in which the human diphtheria toxin (DT) receptor (DTR) is placed under control of a murine tissue-specific promotor, such that delivery of DT selectively ablates cells expressing this high-affinity human DTR; cells expressing only the endogenous low-affinity mouse DTR are assumed to be unaffected. Surprisingly, we found that systemic administration of DT induced rapid regression of murine lung adenocarcinomas that express human mutant EGFR in the absence of a transgenic allele containing human DTR. DT enzymatic activity was required for tumor regression, and mutant EGFR-expressing tumor cells were the primary target of DT toxicity. In FVB mice, EGFR-mutant tumors upregulated expression of HBEGF, which is the DTR in mice and humans. HBEGF blockade with the enzymatically inactive DT mutant CRM197 partially abrogated tumor regression induced by DT. These results suggest that elevated expression of murine HBEGF, i.e. the low-affinity DTR, confers sensitivity to DT in EGFR-mutant tumors, demonstrating a biological effect of DT in mice lacking transgenic DTR alleles and highlighting a unique vulnerability of EGFR-mutant lung cancers.